Critical Thinking Skill for Students: For Better Today and Sustainable Future - Mishra , Jyoti; Sharma, M.P. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
“All of us do not have equal talent but all of us should have an equal opportunity to develop our talent”- John F KennedyHumans are the ultimate creation of nature as they have the ability to think and analyse any situation and take decision on their own. In broad terms, critical thinking is ‘thinking with a purpose’ or thinking for judgement. It seeks to explore questions about current knowledge and a way to find out the solutions of unclear queries therefore critical thinking is considering as a basic life skill. It is a skill to enquire and find out the solution of any unexpected situation or circumstances. Creative thinking, open mindedness and inquisitiveness are included in it. Basically critical thinking deals with knowledge, skill and attitude which are essential for sustainable life and long lasting future. Skill development is an integral part of concept of Education for Sustainable development. It is a future oriented problem solving skill which helps person to exist in workplace confidently. Present paper is an attempt to focus on the concept of critical thinking skill, its relevance and usefulness for students to be successful in their working arena. The researchers have tried to give some recommendations in this direction. Researchers used secondary data from study and various articles, research papers, journals, and online material.